Law in the Digital Age - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (Journal of Sustainability in Integrated Policy and Practice, 2024)
Technology is redefining industries worldwide, and the legal sector is no exception. It has already transformed access to legislation and legal practice. The digital age has transformed the way we interact with each other. In the digital age, law is a rapidly evolving field, reflecting the fast-paced advancements of digital technology. All enacted legislation is now available to anyone with Internet access. This paper introduces the fundamental aspects of law in the digital age.